N-Cinnamoylated Chloroquine Analogues as Dual-Stage Antimalarial Leads - Perez, Bianca C.
The control of malaria is challenged by drug resistance, and new antimalarial drugs are needed. New drug discovery efforts include consideration of hybrid compounds as potential multitarget antimalarials. Previous work from our group has demonstrated that hybrid structures resulting from cinnamic acid conjugation with heterocyclic moieties from well-known antimalarials present improved antimalarial activity. Now, we report the synthesis and SAR analysis of an expanded series of cinnamic acid derivatives displaying remarkably high activities against both blood- and liver-stage malaria parasites. Two compounds judged most promising, based on their in vitro activity and druglikeness according to the Lipinski rules and Veber filter, were active in vivo against blood-stage rodent malaria parasites. Therefore, the compounds reported represent a new entry as promising dual-stage antimalarial leads.